Trends in job quality in Europe. A report based on the fifth European Working Conditions Survey (Luxembourg, 2012)
"Using data from the fifth European Working Conditions Survey (EWCS), this study measures job quality in the 27 countries of the European Union, as well as seven additional countries in Europe that participated in the survey. The intention was to find an objective means of assessing the principle established in a number of EU directives that work should adapt to the workers. Increased understanding of the social costs of poor job quality has focused attention on physical and social environments at work. Prolonged life expectancy and the ageing of the population suggest that jobs will have to be of good quality if more workers are to be persuaded to work longer. The indices constructed for this study do not rely on subjective measurement such as preferences and attitudes, but are built on the self-reported features of jobs that are associated with workers’ well-being."